2012
DOI: 10.4172/2155-6156.1000200
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Remogliflozin Etabonate, a Sodium-Dependent Glucose Co-Transporter-2 Inhibitor, as a Perpetrator of Clinical Drug Interactions: A Study on Drug Transporters and Metabolic Enzymes

Abstract: Type 2 diabetes mellitus is a chronic disease characterized by progressive deterioration of glycemic control and an increased risk of associated complications. Remogliflozin etabonate is the ester prodrug of remogliflozin, a selective sodium-dependent glucose transporter-2 inhibitor that was under development to treat type 2 diabetes. This work investigated the in vitro inhibition of efflux and uptake transporters and cytochrome P450 enzymes by remogliflozin etabonate, remogliflozin and a number of other metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
(60 reference statements)
2
3
0
Order By: Relevance
“…In this study, no effect of remogliflozin etabonate on metformin PK parameters was observed. The findings from this study are consistent with the reported lack of inhibition by remogliflozin etabonate, remogliflozin, and GSK279782 on a panel of metabolic enzymes and transporters, including organic cation transporters involved with metformin renal secretion [39]. …”
Section: Discussionsupporting
confidence: 89%
“…In this study, no effect of remogliflozin etabonate on metformin PK parameters was observed. The findings from this study are consistent with the reported lack of inhibition by remogliflozin etabonate, remogliflozin, and GSK279782 on a panel of metabolic enzymes and transporters, including organic cation transporters involved with metformin renal secretion [39]. …”
Section: Discussionsupporting
confidence: 89%
“…No dose adjustment is required when metformin is coadministered with canagliflozin. The measured metformin concentrations in the current study are comparable to historical steady state values of metformin in published studies …”
Section: Discussionsupporting
confidence: 88%
“…The measured metformin concentrations in the current study are comparable to historical steady state values of metformin in published studies. 21,22 In Study 3, the dose selected is within the recommended dose range for simvastatin. Coadministration of canagliflozin increased the C max of simvastatin (CYP3A4 substrate) by 9% and AUC by 12% while C max of simvastatin acid increased by 26% and AUC by 18%.…”
Section: Discussionmentioning
confidence: 99%
“…This observation provides strong clinical evidence that efflux transporters such as Pgp and breast cancer resistance protein do not limit the intestinal absorption of remogliflozin etabonate, remogliflozin, or metabolites; this is consistent with remogliflozin etabonate being a Biopharmaceutics Drug Disposition Classification System class 1 drug displaying high permeability and solubility (GSK data on file; Benet et al, 2011) and with remogliflozin being a Biopharmaceutics Drug Disposition Classification System class III compound having low permeability and high solubility. However, remogliflozin has demonstrated low central nervous system penetration in the rat, which may be related to Pgp efflux at the blood-brain barrier, its low passive permeability, or other mechanisms (Polli et al, 2012). This is not a concern in humans, because the potential for drug interactions with Pgp inhibitors at the blood-brain barrier is very small (Eyal et al, 2009).…”
Section: Discussionmentioning
confidence: 99%